Psychometric Evaluation of a Patient Experience Questionnaire (PEQ) for Outpatient Appointments: Analysis Using Data from a U.K. National Health Service Audiology Department - Aazh, Hashir; Ballinger, Judith; Hayes, Chloe; Pepler, Anna; Lammaing, Karen; Moore, Brian C. J.; Danesh, Ali A.; Vitoratou, Silia (Journal of the American Academy of Audiology, 2022)
Background The Audiology Department at the Royal Surrey NHS Foundation Trust (RSFT), United Kingdom, developed a patient experience questionnaire (PEQ) to assess and compare patients' experiences of attending a wide range of appointments (e.g., hearing assessment, hearing aid fitting, hearing aid review, tinnitus therapy, balance assessment, and balance rehabilitation).Purpose The aim of this study was to assess the psychometric properties of the PEQ. The PEQ is a unidimensional instrument with four items that assess a patient's experience of an outpatient appointment.Research Design Retrospective cross-sectional study.Study Sample Patients attending appointments for audiology services at RSFT between January and March 2020.Data Collection and Analysis All patients (n = 656) attending appointments for audiology services at RSFT during randomly selected days between January and March 2020 were given the questionnaire to complete themselves (PEQ-self) or to complete on their child's behalf (PEQ-parent). The factor structures for the PEQ-self and PEQ-parent were assessed separately, using confirmatory factor analysis. A multiple-causes, multiple-indicators (MIMIC) model was fitted to explore potential bias due to gender and age. Internal consistency was assessed using Cronbach's α. The bivariate correlations between PEQ scores and other variables were evaluated using the nonparametric Spearman correlation coefficient. Floor and ceiling effects were assessed using the distribution of total scores.Results Confirmatory factor analysis revealed that a one-factor model gave a close fit to the data for both the self and parent versions. Cronbach's α for the total score was 0.77 for the PEQ-self and 0.86 for the PEQ-parent. The MIMIC model showed no significant direct effects of age or gender for either version.Conclusions Both the PEQ-self and PEQ-parent questionnaire can be reliably used to measure patients' experiences of outpatient audiology appointments. Future studies should aim to assess the psychometric properties of the PEQ-self and PEQ-parent for a range of outpatient appointments other than audiology.
Keywords: psychometric; questionnaire; audiology; patient experience